Heróis antigos e modernos: a falsificação para se pensar a história - Lorena Lopes da Costa (2016)
Falsifying is a historical necessity. This historical necessity occurs in contexts in which the rupture with the past is so strong that something familiar to a long tradition must be preserved in the communication of such experience. This thesis chooses two contexts to analyze the falsification process through the hero stories. In common, both contexts have as the major cause of their confrontation with the past the war (morespecifically, the war's new format arising as new technologies become available). From the context of the Peloponnesian War, three tragedies are taken up as object: The Trojan Women (415 BC) and Helen (412 BC) by Euripides and Philoctetes by Sophocles (409 BC). From the second context, in France, the Great War places a new seal upon Odysseus' adventures, which are converted into misfortunes only applicable to someone who has experienced the trenches. The novels analyzed are: Elpénor (1926) by Jean Giraudoux; Naissance de l'Odyssée (1930) by Jean Giono; Les Aventures de Télémaque (1922) by Louis Aragon and Le Retour d'Ulysse (1921) by Valmy-Baysse. Each tragedy or each novel's study tries to figure out how the updating of the hero and his stories are in a close dialogue with the war. From them and from the perception of contemporary needs, we would like to propose how the old stories being updated participate in this falsification process that aids develop the current challenges in a code already known, presenting and endorsing the uniqueness of that necessity.